Daisy's Work: The Third Commandment - Mathews, Joanna H. (Joanna Hooe), 1849-1901 (Salt Lake City, UT : Project Gutenberg, 2014)
"Daisy's Work: The Third Commandment" by Joanna H. Mathews is a children's novel written in the late 19th century. The story follows a young flower girl named Daisy, who embodies innocence and moral integrity while navigating her life on the streets and encountering various characters, including a soldier who learns a powerful lesson about respect and reverence for God's name. The book explores themes of compassion, social class, and the importance of adhering to moral values based on the biblical commandments. At the start of the narrative, we meet Daisy, a delicate and refined flower girl, amidst the chaos of a bustling city. She sells flowers outside a railroad depot, where she often gets noticed by hurried passersby, but is perceived as merely a child of poverty. Her interactions with those around her reveal her kind-hearted nature and her longing for connection, particularly when she encounters a gentleman, General Forster, who becomes intrigued by her. The emotional depth of her character is highlighted when she comforts him regarding his use of profane language, prompting a reflection on the significance of taking the Lord's name in vain, which forms the crux of the lessons imparted throughout the narrative. The opening sets the stage for Daisy$1 (Bs moral teachings and her journey towards understanding her place in the world, making it a poignant read for young audiences. (This is an automatically generated summary.)s
Release date is 2014-01-27
E-text prepared by Melissa McDaniel, Emmy, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Christian life -- Juvenile fiction; Friendship -- Juvenile fiction; Missing children -- Juvenile fiction; Benevolence -- Juvenile fiction; Swearing -- Juvenile fiction; Ten commandments -- Juvenile fiction; Ten commandments -- Name of God -- Juvenile fiction